Private TVET in Africa: Understanding the Context and Managing Alternative Forms Creatively! - Akoojee, Salim (Journal of Technical Education and Training, 2016)
Since the 1990s, there has been a growing sense from both national policymakers and international agencies of the importance of private Technical and Vocational Education and Training and skills provision in all regions. This pri-VET sector both through traditional apprenticeship forms and more formal sector oriented approaches have become an essential feature of the contemporary landscape. It is, however, a sector that is largely undocumented and its regulation is thus based on a less than nuanced understanding of its contribution to both the education and training system in general and as a complement to public TVET provisioning. The paper will seek to identify key features of the key trends of what is known about private TVET provision in Africa with a view to understanding the complexity of provision forms and its current importance in the region. It is argued that for this ‘unconventional education and training’ form to take its place in national systems, there is a need for more rigorous research of the sector to ensure that it is able to take its rightful place in national systems. It is expected that this will enable a more thorough examination of regulatory mechanisms used by governments.